2022
DOI: 10.3390/app12020881
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plant Growth Regulators to Development of the Second Generation Energy Crop Miscanthus × giganteus Produced Two Years in Marginal Post-Military Soil

Abstract: The impact of the plant growth regulators (PGRs) Stimpo, Regoplant, and Charkor on the production of the second-generation energy crop Miscanthus × giganteus on marginal post-military soil was investigated during two vegetation seasons. The land, previously a tank training polygon, has not been in use since 1990 and has become marginal. Biological parameters (stem, shoot, and root lengths) and dry biomass values were evaluated in relation to the applied treatments. The multivariate general linear model (M-GLM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The obtained scientific results contribute to the widespread use of the studied biostimulants in the technology of pea cultivation in the Southern Steppe zone of Ukraine to increase crop productivity and obtain a high-quality crop In experiments with yellow sorghum, V. Karpenko and S. Shutko (2018) proved that the greatest increase in the concentration of green pigments (a and b chlorophylls) and the increase in the net photosynthetic productivity index in leaves was observed when using the herbicide Pik 75 VG in combination with Regoplant. However, V. Pidlisnyuk et al (2022) found no significant effect of Stimpo and Regoplant on the growth and development of Miscanthus × giganteus when grown on depleted soils.…”
Section: Introductionmentioning
confidence: 88%
“…The obtained scientific results contribute to the widespread use of the studied biostimulants in the technology of pea cultivation in the Southern Steppe zone of Ukraine to increase crop productivity and obtain a high-quality crop In experiments with yellow sorghum, V. Karpenko and S. Shutko (2018) proved that the greatest increase in the concentration of green pigments (a and b chlorophylls) and the increase in the net photosynthetic productivity index in leaves was observed when using the herbicide Pik 75 VG in combination with Regoplant. However, V. Pidlisnyuk et al (2022) found no significant effect of Stimpo and Regoplant on the growth and development of Miscanthus × giganteus when grown on depleted soils.…”
Section: Introductionmentioning
confidence: 88%
“…The effect of biostimulants on nematodes was tested in nine-centimeter Petri dishes using IJ and biostimulants were applied at a dose usually used in field conditions (Pidlisnyuk et al 2022). The following concentrations of biostimulants were used: Charkor: Ch1 -0.1%, Ch2 -0.4%; Regoplant: R1 -1.22%, R2 -2.44%; Stimpo: S1 -0.25%; S2 -0.50%.…”
Section: Assessment Of the Direct Impact Of Biostimulants On Entomopa...mentioning
confidence: 99%
“…Likewise, giving the wrong concentration range can cause unexpected effects. In different concentrations, growth regulators can have the opposite effect, sometimes inhibiting plant growth because they cause toxicity to all plant tissues (Pidlisnyuk et al 2022). In this case, it was assumed that there was an interaction of concentration and the right type of PGR, resulting in better diameter growth of the upper hypocotyl cuttings.…”
Section: Increase In Diameter Of Rhizophora Apiculatamentioning
confidence: 99%